Uma visão sobre a aquisição do léxico e da sintaxe em língua materna - Brasil, Angela Medeiros de Assis; Santos, Rogéria Lourenço dos (Linguagens & Cidadania, 2017)
This paper aims to bring theoretical discussion about the main aspects of child’s development concerning lexical and syntax acquisition. In order to do so, the authors whom we bring to discussion are Griffiths (1997), Karmiloff-Smith (1997), Perera (1997), Peters (1997), Bassano (2000) and Kail (2000). Our purpose is to make a brief overview of the topic to reinforce the importance of knowing how children develop their language. Once teachers have clear in mind the levels of this development they will be more able to work with children in their first or second language acquisition.